The Supervision Role of Independent Commissioner in Decreasing Risk From Earnings Management and Debt Policy - Muhammad Aulia Ramadhan; Amrie Firmansyah (Accounting Analysis Journal, 2022)
Purpose : This study examines the effect of earnings management and debt policy on financial distress. In addition, this study examines the role of the independent commissioner as a moderating variable in the relationship between the independent and dependent variables. Financial distress in this study employs the Altman model (1968) modified by Graham et al. (1998) which has a high prediction rate, above 60 percent, and its size has been used in various countries. Earnings management in is study employs the model of Kothari et al. (2005), known as the Performance-Matched Discretionary Accruals model. The advantage of the model is that it can measure earnings management more accurately. Using independent commissioners as a moderating variable in the association between earnings management and debt policies on financial distress is rarely used in previous studies. Method : This study uses a quantitative method approach. The research data is sourced from consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) financial statements. Research data sourced from www.idx.co.id and www.idnfinancials.com. Based on purposive sampling, the research sample consisted of 138 observations from 46 companies from 2018 to 2020. Hypothesis testing was carried out using multiple linear regression for panel data. Findings : The results of this study indicate that earnings management has a negative effect on financial distress, while debt policy has a positive effect on financial distress. This study also finds that independent commissioners can attenuate the negative effect of earnings management on financial distress. Still, independent commissioners cannot have a moderating effect on the relationship between debt policy and financial distress. Novelty : This study places independent commissioners, which have greatly influenced a company’s management performance, as a moderating variable in testing earnings management and debt policies on financial distress, which are rarely used in previous studies. Keywords: Financial Difficulties; Earnings Quality; Capital Structure; Corporate Governance